Smoking, Vaping, and the Benefits Cessation in Times of COVID-19: A Public Health Perspective - Mungia, Rahma; Valdez, Danielle Nicole (Frontiers in Dental Medicine, 2020)
The goal of this article is to inform dental practitioners and specialists of the benefits of smoking and vaping cessation in relation to COVID-19 transmission. COVID-19 caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) has affected more than 31.7 million people globally with infection rates continuing to rise rapidly. Smoking dramatically impairs lung function and gives rise to an increase in susceptibility for infection, allowing for a more difficult recovery due, in part, to the damage SARS-CoV-2 does to the lungs. Tobacco smoking is one of the primary causes of death in the United States (US), however, nearly 40 million adults still smoke cigarettes, with 4.7 million middle and high school students using at least one tobacco product, including electronic cigarettes. COVID-19 is transmitted through salivary droplets causing severe bilateral pneumonia and significantly reduced lung function, putting smokers and vapers at greater risk through cross-contamination and face touching. So far, data from animal studies suggests that vaping leads to an increased susceptibility to infection, which coincides with evidence of increased rates of chronic bronchitis in vapers. There is yet to be data regarding the benefits of smoking and vaping cessation during the COVID-19 pandemic. However, there is evidence suggesting that 4 weeks or more of smoking cessation intervention reduces the risk of contracting COVID-19 and developing severe complications. Because of these probable connections, dental practitioners should advise their patients to stop smoking and/or vaping via the 5 A’s cessation strategy.